2015
DOI: 10.3390/molecules200814103
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Underlying Mechanism of Sulfone Derivatives Containing 1,3,4-oxadiazole on Citrus Canker

Abstract: Abstract:The objectives of the current study were to isolate and identify the pathogen responsible for citrus canker and investigate the efficacy of sulfone derivatives containing 1,3,4-oxadiazole moiety on controlling citrus canker caused by Xanthomonas citri subsp. citri (Xcc) under in vitro and field conditions. In an in vitro study, we tested eight sulfone derivatives against Xcc and the results demonstrated that compound 3 exhibited the best antibacterial activity against Xcc, with a half-maximal effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…On the other hand, sulfone derivatives containing 1,3,4oxadiazole were tested in vitro and in field conditions to control X. citri growth (Li et al 2015;Wang et al 2018). After exposing navel oranges to three rounds of spray with 1,3,4oxadiazole, a 60-64% reduction in citrus canker was observed, compared to a 50-56% reduction obtained with copper-based compounds (Li et al 2015).…”
Section: Amphiphile Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, sulfone derivatives containing 1,3,4oxadiazole were tested in vitro and in field conditions to control X. citri growth (Li et al 2015;Wang et al 2018). After exposing navel oranges to three rounds of spray with 1,3,4oxadiazole, a 60-64% reduction in citrus canker was observed, compared to a 50-56% reduction obtained with copper-based compounds (Li et al 2015).…”
Section: Amphiphile Compoundsmentioning
confidence: 99%
“…On the other hand, sulfone derivatives containing 1,3,4oxadiazole were tested in vitro and in field conditions to control X. citri growth (Li et al 2015;Wang et al 2018). After exposing navel oranges to three rounds of spray with 1,3,4oxadiazole, a 60-64% reduction in citrus canker was observed, compared to a 50-56% reduction obtained with copper-based compounds (Li et al 2015). In addition, when 1,2,4-triazole was combined with quinazolones, another class of antimicrobial molecules, a series of derivatives inhibited X. citri growth more effectively than the tested controls bismerthiazol and thiadiazol-copper (Fan et al 2018;Patel et al 2018).…”
Section: Amphiphile Compoundsmentioning
confidence: 99%
“…A series of 2,5‐disubstituted‐1,3,4‐oxadiazole/thiadiazole sulfone derivatives were synthesized by Li et al 48,49 Antibacterial bioassay results indicated that compound 23 (Figure 13) demonstrated the best in vitro antibacterial bioactivities against Xoo , Xoc , and Xac , with the EC 50 values of 1.07, 7.14, and 1.23 μg/mL, respectively, which were better than those of kocide 3000, bismerthiazol, and thiodiazole copper. Meanwhile, in vivo antibacterial activity tests at greenhouse conditions demonstrated that the controlling effects of compound 23 against rice bacterial leaf blight were better than those of bismerthiazol and thiodiazole copper.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…An efficient way that promotes the agrochemical discovery processes is to expand the amount and breadth of targets. Currently, a chemical proteomic technique termed “activity-based protein profiling” (ABPP) was widely exploited to unravel the protein targets and consequently stimulated and promoted the effective discovery of novel drugs both in the medical and agricultural fields. Oxadiazole sulfone reagents represent a class of novel structures and exhibit broad-spectrum biological activities, such as antibacterial, antifungal, and antiviral activities . Among these structures, the candidate jiahuangxianjunzuo ( JHXJZ ) and its analogues indicate potent antibacterial activity against those uncontrollable diseases, including tobacco bacterial wilt. ,,, Our previous study identified that dihydrolipoamide S -succinyltransferase (DLST) is a major target of JHXJZ in Xanthomonas, such as Xanthomonas oryzae pv.…”
Section: Introductionmentioning
confidence: 99%